Aladdin (Grolier New York, 2002)
An illustrated storybook of Disney's film "Aladdin," which is packed with adventure and humor and a cast of colorful characters that includes a beautiful princess, a crafty monkey, a treacherous villain, a poor young boy who dreams of a better life and a wise-cracking genie.